Pengaruh Pemberian Ekstrak Daun Sirih (Piper betle L.) untuk Mengendalikan Damping-Off pada Tanaman Cabai Capsicum annum) - Hidayat, Taufiq; Supriyadi, Supriyadi; Sarjiyah, Sarjiyah (Universitas Muhammadiyah Yogyakarta, 2015)
Sclerotium roflsii is the causal agent of damping-off disease on pepper which difficult to control. The use of chemical pesticides cause several damage to the environment. The used of Piper betle leaves extract which is contains antifungal compounds becomes one of the solution. The aim of this study to obtain the optimum concentration of piper betle leaves extract and dipping periode of chili seed in leaves extract to control damping off disease caused by Sclerotium rolfsii. The study consists of two experiments. The first experiment was isolation and multiplication of damping off disease in chilli, this stage was conducted in laboratorium. The second experiment was performed to investigate effectivity of piper betle leaf extract to control damping off using dipping method, this stage conducted in Greenhouse. The study arranged in Completely Randomized Design (CRD) with single factor experimental design consist of 13 treatment, namely consentration of 0%, 40%, 60% and 80% Piper betle leaves extract (v/v) with 1 hour, 2 hour, and 3 hour dipping time. The result showed that Piper betle leaves extract of 60% with 1 hour dipping time had the best ability among the other treatment to control damping off disease cause of Sclerotium rolfsii in chili seedlings.